Comparative Mapping Combined With Map-Based Cloning of the Brassica juncea Genome Reveals a Candidate Gene for Multilocular Rapeseed - Chen, Cuiping; Xiao, Lu; Li, Xin; Du, Dezhi (Frontiers in Plant Science, 2018)
Multilocular traits exist in a variety of plants and exert important effects on plant yield. Previous genetic studies have shown that the multilocular trait of the Brassica juncea cultivar Duoshi is controlled by two recessive genes, Bjln1 and Bjln2. In this species, the Bjln1 gene is located on chromosome A07, and the Bjln1 candidate gene is BjuA07.CLV1. In this study, a BC4 mapping population for the Bjln2 gene was generated. This population was used to construct genetic linkage maps of the Bjln2 gene by amplified fragment length polymorphism (AFLP), intron length polymorphism (IP) and simple sequence repeat (SSR) methodology. The results showed that the Bjln2 gene was restricted to a 0.63 cM interval. BLAST alignment with B. juncea revealed the Bjln2 gene was located within an 11.81-16.65 Mb region on chromosome B07. Moreover, the candidate gene BjuB07.CLV1 (equivalent to Bjln2) was cloned by comparing mapping and map-based cloning results, and the BjuB07.CLV1 gene has the ability to restore the bilocular traits by genetic complementation experiment. The sequencing revealed that a 4961 bp insertion interrupted the coding sequence of the BjuB07.CLV1 gene, resulting in an increase in locule number. Expression analysis revealed that BjuB07.CLV1 was expressed in all tissues and that its expression level in bilocular plants was significantly higher than that in multilocular plants. In addition, markers closely linked to the Bjln2 gene were developed and used for molecular marker-assisted breeding of multilocular traits.